The Influence of Products, Prices, Promotions, and Places on Purchase Decisions at PT. Arta Agrindo Subur Pratama Pekanbaru - Chandra, Stefani; Tianto, Agus; Veronica, Veronica; Ng, Martha; David, David (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The purpose of this study was to analyze the effect of product, price, promotion and place on purchasing decisions at PT Arta Agrindo Subur Pratama Pekanbaru. The population in this study were all customers who bought fertilizer at PT Arta Agrindo Subur Pratama Pekanbaru. The sampling technique used is the proposive sampling method. The sample size of this study was 80 respondents who were customers of PT Arta Agrindo Subur Pratama Pekanbaru. The data analysis technique used is multiple linear regression. The results of this study indicate that product, price, promotion have a positive and significant effect on purchasing decisions while place has no significant effect on purchasing decisions.